A fluorescent fingerprint recording strategy for complex chemical solution. Issue 7 (25th January 2019) - Duan, Qiannan; Lee, Jianchao; Zheng, Chaoqun; Zheng, Yunyun; Chen, Han
Abstract : Fluorescent fingerprint recording strategy based on the PEL-chip: a data-bridge between complex chemical solution (CCS) and its digital analysis. Abstract : A fluorescent fingerprint recording strategy for complex chemical solution (CCS) analysis was proposed. Using ink-jet printing technology, the feature information of the CCS was expressed by fluorescence imaging method. Obtained fluorescent fingerprint images (named PEL-image) might provide some possible interlinks among different samples by the digital image analysis.